Coccidiosis in Barbari and Jamunapari goats at an organized farm in semi-arid tropical region of India - SINGH, ALOK KUMAR; SHANKER, DAYA; ROUT, PRAMOD KUMAR; KUMAR, ASHOK; KUMAR, PRADEEP (The Indian Journal of Animal Sciences, 2023)
The aim of the present study was to learn more about caprine coccidiosis in semi-arid tropical regions, including transformation techniques for data analysis and variables impacting faecal oocyst count in Barbari and Jamunapari goats. For this investigation, a total of 1422 goat faeces samples from two separate seasons were tested, and 1342 (94.37%) of them were positive for several coccidian species oocysts. A total of 259 animals, including 153 Barbari (77 males and 76 females) and 106 Jamunapari (45 males and 61 females), provided the 777 faecal samples from the autumn season. In contrast, 215 animals, including 110 Barbari (60 males and 50 females) and 105 Jamunapari (52 males and 53 females), provided the 645 faecal samples from the spring season. At 3.5, 6.0, and 7.5 months of age, both breeds had their faeces examined. The geometric mean of oocysts per Gram (OPG) for the Barbari breeds was greater than the Jamunapari breeds at 6.637a±0.03 (662) and 6.521b±0.03 (579), respectively. The Transformed oocysts per gram (LOPG) was also greater in females 6.651a±0.03 (673) than in males. Similar to the age comparison, the 7.5 month older animal showed a greater count of 6.858a±0.04 (851) than the 3.5 and 6.0 month old animals. The five found coccidian oocysts were Eimeria arloingi, Eimeria ninakohlyakimovae, Eimeria hirci, Eimeria caprina, and Eimeria christenseni. The oocysts Eimeria arloingi (39–45%), Eimeria ninakohlyakimovae (25–31%), Eimeria hirci (13-20%), Eimeria christenseni (6–12%), and Eimeria caprina (3–10%) were present in both breeds and seasons of male and females.